DETERMINATION OF RISK MINIMIZATION STRATEGY FOR HERBAL DRINK PRODUCTION WITH GMP APPROACH USING SCORING AND AHP - Ratining Indah Wardani; Imam Santoso; Riska Septifani (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Herbal drinks such as herbs have become part of the culture in Indonesia. The herbal plants processed into herbal drinks include bilimbi fruit (Averrhoa bilimbi L.) and secang (Caesalpinia sappan L.). This study aims to determine the risk minimization strategy in producing herbal drinks in CV XYZ by analyzing 14 aspects of Good Manufacturing Practices (GMP) using a scoring form and the Analytical Hierarchy Process (AHP) method. The scope of GMP in this study orients to how to produce good processed food. Determination of risk minimization strategy using the Analytical Hierarchy Process (AHP) method. The assessment results in applying GMP in CV XYZ using scoring calculation gotten three aspects with the highest deviation, “the sufficient qualify category